Evaluation of accuracy and time taken to make an open tray implant impressions with two techniques - M Sai Teja Reddy; Nabeel Ahmed; Subhabrata Maiti; Dhanraj M Ganapathy (Wolters Kluwer Medknow Publications, 2022)
Implant dentistry's emergence and acceptance have provided physicians with a wide range of new options for fixed and removable rehabilitation. The eventual replacement of the lost tooth is the ultimate success, and this can be accomplished using recognized prosthodontic methods. The present study aims to evaluate the time and dimensional accuracy of implant definitive models with an open tray impression with two different techniques. Impression was made in two different techniques and the cast was poured and checked for the time taken and the accuracy of the impression. In IBM SPSS software version 23.0 all the results were statistically analyzed. An Independent t-test was performed for the parameters. No statistically significant difference was present (P > 0.05) when comparing the accuracy and time taken between the two groups. It is concluded that time taken and the misfit is less for modified open tray impression techniques when compared to the regular open tray impression.